Evaluating the link between antenatal care and foetal outcomes in a rural tertiary care center in North India - Ahmad, Rizwan; Srivastava, Mridula; Rathoria, Ekansh; Rathoria, Richa; Sattar, Aatif (International Journal of Contemporary Pediatrics, 2025)
Background: Antenatal care (ANC) is essential for safeguarding the health of both mothers and newborns. Despite policy initiatives, rural India continues to face challenges in ensuring adequate and quality ANC. This study assessed the adequacy of ANC using a structured scoring system and examined its association with foetal outcomes in a rural tertiary care center in North India. Methods: This cross-sectional study was carried out in a hospital setting, enrolling 175 mothers and their infants between August 2023 and January 2025. ANC quality was measured using a 10-domain scoring system (maximum score 40). Adequate ANC was defined as ≥24 points. Maternal and neonatal outcomes, including birth weight, Apgar scores, preterm delivery, and neonatal intensive care unit (NICU) admission, were compared between adequate and inadequate ANC groups. Results: The mean ANC score was 24.95±8.27; 73.7% of women received adequate ANC. Adequate ANC was significantly associated with higher socioeconomic status, booked status, and caesarean deliveries (p<0.001). Neonates of inadequately supervised pregnancies had significantly higher odds of preterm birth (OR=24.8, p<0.001), low birth weight (OR=45.8, p<0.001), low Apgar score at 1 minute (OR=6.3, p=0.012), and NICU admission (OR=0.08, p<0.001). Conclusions: Adequate ANC, as measured by a structured scoring system, was strongly associated with favourable foetal outcomes. Strengthening maternal health programs should emphasize early registration, comprehensive ANC contacts, improved record completeness, and quality counselling. Addressing socioeconomic barriers and promoting equitable access to ANC remain essential to reduce adverse outcomes in rural populations.